Analisis Strategi Marketing Mix Dalam Meningkatkan Penjualan Pada Coffee Shop The Liter Di Summarecon Bekasi - Zahra Aliyanti, Dila; Cholik, M. Agus (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Marketing strategies play an important role in achieving business success, as these areassignificantly contribute to the realization of a business plan that helps maintain and increase saleswhile securing market positions by leveraging opportunities and strengthening sales through theimplementation of marketing mix strategies. The researchers used a qualitative approach to involveresearchers in gaining a better understanding of complex and contextual phenomena to report adetailed perspective from informant sources in the research environment, focusing mainly on thephenomenon of marketing strategy in the concept of the marketing mix theory in increasing salesat the coffee shop The Liter at Summarecon Bekasi. The marketing mix strategy for boosting salesat The Liter coffee shop has produced positive consumer feedback through direct communicationin the store and interaction through social media. However, the lack of activity in social media hasresulted in many consumers still not realizing the existence of the brand The Liter. There is nospecial online booking application in The Liter and no consumer membership program; there is noevent that attracts the general consumer because it is only scheduled for a special event of K-Popfans; the menu offered by The Liter is very monotonous; there is no update of special beveragevariants, so consumers get bored.